Chylomicrons enhance endotoxin excretion in bile. - Read, T E (1993)
Chylomicrons prevent endotoxin toxicity and increase endotoxin uptake by hepatocytes. As a consequence, less endotoxin is available to activate macrophages, thereby reducing tumor necrosis factor secretion. To determine whether the chylomicron-mediated increase in hepatocellular uptake of endotoxin results in increased endotoxin excretion into bile, we examined bile after endotoxin administration. A sublethal dose (7 micrograms/kg) of 125I-endotoxin was incubated with either rat mesenteric lymph containing nascent chylomicrons (500 mg of chylomicron triglyceride per kg of body weight) or an equal volume of normal saline (controls) for 3 h and then infused into male Sprague-Dawley rats. Bile samples were collected via a common bile duct catheter for 24 h. Infusion of endotoxin incubated with chylomicrons increased biliary excretion of endotoxin by 67% at 3 h (P < or = 0.006) and by 20% at 24 h (P < or = 0.01) compared with infusion of endotoxin incubated in saline. Endotoxin activity, as measured by the Limulus assay, was not detected in the bile of test animals. However, endotoxin activity was detected after hot phenol-water extraction of bile, demonstrating that endotoxin is inactive in the presence of bile but retains bioactivity after hepatic processing. Since the majority of an intravenous endotoxin load has been shown to be cleared by the liver, acceleration of hepatocyte clearance and biliary excretion of endotoxin may represent a component of the mechanism by which chylomicrons protect against endotoxin-induced lethality.